2004
DOI: 10.1016/s0166-8641(03)00211-6
|View full text |Cite
|
Sign up to set email alerts
|

On the multitude of monoidal closed structures on UAP

Abstract: In this note, we prove that all compact Hausdorff topological spaces are exponential objects in the category UAP of uniform approach spaces and contractions as introduced in R. Lowen, Approach Spaces: the Missing Link in the Topology-Uniformity-Metric Triad, Oxford University Press, 1997. As a consequence, we show that UAP admits at least as many monoidal closed structures as there are infinite cardinals. We also prove that under the assumption that no measurable cardinals exist, there exists a proper conglome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Exponentiable objects in approach theory are studied in [21,14], and the following sufficient condition is obtained.…”
Section: Corresponding Morphisms In Related Categoriesmentioning
confidence: 99%
“…Exponentiable objects in approach theory are studied in [21,14], and the following sufficient condition is obtained.…”
Section: Corresponding Morphisms In Related Categoriesmentioning
confidence: 99%
“…This fact triggers the question of finding sufficient and necessary conditions for an approach space X to be exponentiable, that is, for the cartesian product functor (−) × X : App → App to have a right adjoint. A first important result in this direction was obtained in [Lowen and Sioen, 2004] where it is shown that every compact Hausdorff spaces is exponentiable in the category of uniform approach spaces and contractions. Two years later, [Hofmann, 2006] presents a sufficient condition motivated by the characterisation of exponentiable generalised metric spaces obtained in Clementino and Hofmann [2006] (see Theorem 4.4).…”
Section: Introductionmentioning
confidence: 99%